The grape entomology - Mani, M. (Springer India, 2014)
Intensive and extensive cultivation of grapes (Vitis vinifera L.) leads to serious pest problem in vineyards in major grape growing areas of the world. Climatic conditions in India are favorable for high production of table and wine grapes, and thus also for incidence of variety of pests. These include the sucking insect pests namely thrips, hoppers, mealybugs etc., and beetle pests like stem borer, stem girdler, flea beetles, chafer beetles, shot hole borer and several lepidopteron, mites, nematodes and vertebrate pests. Pests of grapes in other countries relevant to Indian conditions are also dealt herewith since they may get introduced in India in future. Up to date information on biology, damage, seasonal development, management practices of the pests are covered in this book. Some of the pest management practices followed in other countries are also given, which will be useful to Indian conditions. Pesticide residue is a serious problem both for export and internal market in grapes. Guideline for pesticide residue management in grapes is also given in this book. The authors have tried to accommodate almost all the important information generated on the grape pests up to 2012. A complete list of grape pests (except disease) occurring in different grape growing regions of the world is also covered in this book which will be ready reckoner for the grape workers. The authors sincerely hope that this book will provide useful information to many entomologists, students working on grapes and the grape growers in the country. It is a pleasure to thank all those people who gave help, suggestions and encouragement in the preparation of our book "The Grape Entomology".